Fact or fiction: The "four-uns" of geriatrics - Doreen Bauer (AOSIS, 1982)
An edited version of a paper presented to the SASP whilst the author was Guest Lecturer at the University of Stellenbosch, this article presents a positive viewpoint about physiotherapy services for elderly people. There is a great deal of challenges, and potential reward, in geriatric physiotherapy, but therapists must be appropriately educated, creative and enthusiastic. A rapidly increasing elderly population, which will include physiotherapists, demands a more active contribution from physiotherapists if unnecessary dependency is to be prevented or ameliorated. .